Damage Burden in Polish Patients with Antiphospholipid Syndrome Measured Using Damage Index for Antiphospholipid Syndrome (DIAPS) - Ewa Haladyj; Barbara Stypinska; Agata Matusiewicz; Wojciech Kunisz; Marzena Olesinska; Agnieszka Paradowska-Gorycka (Biomedicines)
Objectives: We aimed to quantify the damage burden measured using the Damage Index for Antiphospholipid Syndrome (DIAPS) in patients with antiphospholipid syndrome (APS) and identify patients with high damage as well as any correlations of damage with subclinical atherosclerosis. Methods: Patient damage was assessed via DIAPS. Based on demographic, clinical and laboratory characteristics, patients were divided into two subgroups: thrombotic APS patients with high vs. low damage, and non-thrombotic aPL-positive patients with vs. without damage. Participants underwent carotid/femoral ultrasound for atherosclerotic plaque detection and carotid–femoral and carotid-radial pulse wave velocity (PWV). Results: We included 112 patients with an APS diagnosis, 57 (50.9%) with primary APS and 55 (49.1%) with associated SLE. Cardiovascular (CVD) risk factors and complications were significantly more frequent in the thrombotic group, as well as in patients with high damage within the thrombotic group. We did not identify any risk factors for increased damage in the non-thrombotic group. Atherosclerotic plaque presence was present in 27 (24%) of the patients in this study with the same frequency in the APS and APS/SLE groups (p = 0.5446). Pulse wave velocity (PWV) was elevated in 27–32% patients according to analyzed arteries. Elevated PWV was more frequent in the APS group in comparison to APS/SLE only between carotid and radial arteries (p = 0.0012). Both atherosclerotic plaque presence and PWV did not correlate with damage severity. Conclusions: DIAPS indicates substantial damage in APS patients in our study. High organ damage mainly affected thrombotic patients and was related to CVD complications. At the same time, screening of subclinical atherosclerosis seems not to predict higher damage in APS patients.